Microwave-assisted Impregnation of Zinc Metal Ions on Surface of Quenched Pulverized Shrimp Shell Waste - Dwindrata Basuki Aviantara; Fuzi Suciati; Gunawan Hadiko; Nastiti Siswi Indrasti; Mohamad Yani (International Journal of Technology, 2024)
This study evaluated the effects of microwave irradiation on the impregnation efficiency of zinc onto pulverized shrimp shell waste. Prior to impregnation, the pulverized shrimp shell was heat treated at 350, 450, and 550 oC for 1, 2 and 3 hours. After each treatment, the treated pulverized shrimp shell was immediately quenched in liquid nitrogen. Microwave-assisted impregnations were carried out at 80 oC for 10, 20, and 30 minutes and at 50% and 100% of the maximum delivery power rate of the laboratory microwave equipment. The resulting impregnated solids were characterized via TGA, DTA, FTIR, SEM, and XRD. Semi-quantitative measurement of the impregnated zinc was determined based on XRF analysis. The BET analysis of the original pulverized shrimp shell waste provided a surface area of 1.273 m2/g and achieved 30.423 m2/g after 550 oC for 3h heating treatment. An increase in crystallinity index was detected as the pulverized shrimp shell waste was exposed to higher and prolonged heating temperatures. Statistical analysis showed no significant difference (p = 0.05) in impregnated zinc levels among the heat-treated pulverized shrimp shells for the same power output of microwave energy. However, a significant difference was obtained between 50% and 100% power output, of which the latter can impregnate two-fold higher levels of zinc than the former. The results of this study concluded that the microwave-assisted technique might potentially be applied for metal impregnation for the preparation of heterogeneous catalysts, and the power strength of the microwave plays a prominent role in metal impregnation.